Kekerasan Ibu Tiri Terhadap Anak Tiri Dalam Cerita "Nenek Pakande": Stepmother’s Violence Against Stepchild In The Story Of “Nenek Pakande” - Amir Mahmud (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2022)
The study aims to describe the stepmother's act of violence against her stepchild. The problem of this study is why does the stepmother commit act of violence against her stepchild? The researcher uses a descriptive qualitative method due to the data analysis is in the form of words, phrases, sentences, and paragraphs that inform the purpose of the stepmother commits violence against her two stepchildren. The study uses feminism theory which focuses on the purpose of stepmother in committing household violence. The results of this study have found two types of violence, namely psychological and verbal violence. The stepmother commits violence act by scaring, threatening, and yelling so that her two children leave the house forever then the stepmother can freely develop her potential and control her husband's garden income.